Early inflammatory response following elective abdominal aortic aneurysm repair: A comparison between endovascular procedure and conventional, open surgery - Marjanović Ivan; Jevtić Miodrag; Mišović Sidor; Vojvodić Danilo; Zoranović Uroš; Rusović Siniša; Šarac Momir; Stanojević Ivan (Vojnosanitetski Pregled)
Background/Aim. Abdominal aorta aneurysm (AAA) represents a pathological enlargment of infrarenal portion of aorta for over 50% of its lumen. The only treatment of AAA is a surgical reconstruction of the affected segment. Until the late XX century, surgical reconstruction implied explicit, open repair (OR) of AAA, which was accompanied by a significant morbidity and mortality of the treated patients. Development of endovascular repair of (EVAR) AAA, especially in the last decade, offered another possibility of surgical reconstruction of AAA. The preliminary results of world studies show that complications of such a procedure, as well as morbidity and mortality of patients, are significantly lower than with OR of AAA. The aim of this paper was to present results of comparative clinical prospective study of early inflammatory response after reconstruction of AAA between endovascular and open, conventional surgical technique. Methods. A comparative clinical prospective study included 39 patients, electively operated on for AAA within the period of December 2008 - February 2010, divided into two groups. The group I counted 21 (54%) of the patients, 58-87 years old (mean 74.3 years), who had been submited to EVAR by the use of excluder stent graft. The group II consisted of 18 (46%) of the patients, 49-82 (mean 66.8) years, operated on using OR technique. All of the treated patients in both groups had AAA larager than 50 mm. The study did not include patients who have been treated as urgent cases, due to the rupture or with simptomatic AAA. Clinical, biochemical and inflamatory parameters in early postoperative period were analyzed, in direct postoperative course (number of leucocytes, thrombocytes, serum circulating levels of cytokine - interleukine (IL)-2, IL-4, IL-6 and IL-10). Parameters were monitored on the zero, first, second, third and seventh postoperative days. The study was approved by the Ethics Commitee of the Military Medical Academy. Results. The study showed a statistically significantly shorter time of treatment in the EVAR group (average 90 min) compared to the OR group (average 136 min). Also, there was a statistically significantly less blood loss in the patients operated on by the use of EVAR surgery (average 60 mL) as compared to the patients treated with OR techinique (average 495 mL), as well as a shorter postoperative hospitalization of patients in the EVAR group (average 4 days) compared to the OR group (average 8 days). The OR group was detected with a statistically significant increase of leucocytes and statistically significant fall of the number of thrombocytes in comparison with the EVAR group in all the investigated terms. A significant concentration rise of IL-2 in the OR group and concentration rise of IL-6 in the EVAR group was shown 24 hours after the procedure, whereas on the second postoperative day there was detected a significant fall of IL-6 in the EVAR group. IL-4 concentration in the OR group was significantly higher as of the third postoperative day in comparison to the EVAR group. There was no significant difference in IL-10 concentration between the groups. Conclusion. The EVAR techinique is a safer and less invasive and less traumatic procedure for patients than the OR of AAA. Following the EVAR, there are less inflammatory reactions in the early postoperative periodas compared to the OR and therefore less possibility of the development of systemic inflammatory respons syndrome in patients treated.